Perbandingan Algoritma Contraharmonic Mean Filter dan Arithmetic Mean Filter untuk Mereduksi Exponential Noise - Mhd Furqan; Sriani Sriani; Yuli Kartika Siregar (JISKA (Jurnal Informatika Sunan Kalijaga), 2020)
Noise in the image caused a decrease in image quality, so that the image will look dirty and spots appear on the resulting image. Noise also results in reduced information on the resulting image so that noise limits valuable information when image analysis is performed. Filtering technique is one way to overcome noise. The filtering technique used in this study is using the Contraharmonic Mean Filter algorithm and the Arithmetic Mean Filter algorithm with the type of noise used to reduce the Exponential Noise. The results of the two algorithms show that the Arithmetic Mean Filter algorithm is a better algorithm to reduce the Exponential Noise compared to the Contraharmonic Mean Filter algorithm which is proven based on the value of MSE (Mean Square Error) and PSNR (Peak Signal-to-Noise Ratio).